Characterization of ALBA Family Expression and Localization in Arabidopsis thaliana Generative Organs - Náprstková, Alena; Malínská, Kateřina; Záveská Drábková, Lenka; Billey, Elodie; Náprstková, Dagmar; Sýkorová, Eva; Bousquet-Antonelli, Cécile; Honys, David (International journal of molecular sciences, 2021)
ALBA DNA/RNA-binding proteins form an ancient family, which in eukaryotes diversified into two Rpp25-like and Rpp20-like subfamilies. In most studied model organisms, their function remains unclear, but they are usually associated with RNA metabolism, mRNA translatability and stress response. In plants, the enriched number of ALBA family members remains poorly understood. Here, we studied ALBA dynamics during reproductive development in Arabidopsis at the levels of gene expression and protein localization, both under standard conditions and following heat stress. In generative tissues, ALBA proteins showed the strongest signal in mature pollen where they localized predominantly in cytoplasmic foci, particularly in regions surrounding the vegetative nucleus and sperm cells. Finally, we demonstrated the involvement of two Rpp25-like subfamily members ALBA4 and ALBA6 in RNA metabolism in mature pollen supported by their co-localization with poly(A)-binding protein 3 (PABP3). Collectively, we demonstrated the engagement of ALBA proteins in male reproductive development and the heat stress response, highlighting the involvement of ALBA4 and ALBA6 in RNA metabolism, storage and/or translational control in pollen upon heat stress. Such dynamic re-localization of ALBA proteins in a controlled, developmentally and environmentally regulated manner, likely reflects not only their redundancy but also their possible functional diversification in plants.
Keywords: PABP3; proteiny vázající RNA; fyziologický stres; proteiny huseníčku; poly(A)-vazebné proteiny; Promoter Regions, Genetic; Microscopy, Confocal; Poly(A)-Binding Proteins; heat stress; reakce na tepelný šok; flowering; expression analysis; konfokální mikroskopie; Arabidopsis thaliana; Arabidopsis Proteins; regulace genové exprese u rostlin; ALBA; Gene Expression Regulation, Plant; Stress, Physiological; Arabidopsis; Heat-Shock Response; protein localization; Pollen; pollen development; Flowers; květy; confocal microscopy; pyl; RNA-Binding Proteins; promotorové oblasti (genetika)